New α-galactosidase-inhibiting aminohydroxycyclopentanes. Issue 26 (29th April 2021) - Weber, Patrick; Fischer, Roland; Nasseri, Seyed A.; Stütz, Arnold E.; Thonhofer, Martin; Withers, Stephen G.; Wolfsgruber, Andreas; Wrodnigg, Tanja M.
Abstract : A concise and robust synthesis of new cyclopentanoid competitive inhibitors of α-galactosidases related to Fabry's disease and other α-galactosidase related disorders. Abstract : A set of cyclopentanoid α-galactosidase ligands was prepared from a partially protected ω-eno-aldose via a reliable (2 + 3)-cycloaddition protocol with slightly modified conditions. The obtained N -benzylisoxazolidine ring was selectively opened and the configuration of the hydroxymethylgroup was inverted. Consecutive deprotection provided an aminocyclopentane, which was N -alkylated to furnish a set of potential α-galactosidase inhibitors. Their glycosidase inhibitory activities were screened with a panel of standard glycosidases of biological significance.